Miłość i nienawiść (głównie jednak nienawiść) w Nowym Świecie. Wizja kolonizacji angielskiej w Ameryce Północnej w filmie Terence’a Malicka - Hlebowicz, Bartosz (Er(r)go. Teoria - Literatura - Kultura, 2013)
Bartosz Hlebowicz Love and Hate (But Mostly Hate) in the New World. Vision of English Colonization in North America in Terence Malick’s Film. Terence Malick’s The New World retells the story of Pocahontas and John Smith and the founding of Jamestown, Virginia, the latter considered to initiate the period of British colonization of North America. Of the historical Pocahontas, the daughter of Wahunsunacawh (more famous as Powhatan), the chief of the Virginia tribes, we really do not know too much, but the popular image of the “Indian princess” and lover of the soldier-colonist has become all too well known. Malick is not trying to be very original in his version of the Pocahontas myth—it seems that retelling her story is merely a pretext to portray an imagined, almost ideal native community and contrast it with the chaotic and violent world of white settlers. Paradoxically, in this audibly and visually enchanting narration some basic truth about the founding days of the American nation is convincingly transmitted: that the root of the nation’s foundation is to be seen not in the alleged love of two individuals coming from two different cultures, but in the growing misunderstanding, distrust and hatred between the two races.